Symplastic Phloem Loading in Poplar . Issue 1 (23rd July 2014) - Zhang, Cankui; Han, Lu; Slewinski, Thomas L.; Sun, Jianlei; Zhang, Jing; Wang, Zeng-Yu; Turgeon, Robert
Abstract : Sucrose enters the phloem in poplar leaves through plasmodesmata . Abstract: Sap is driven through phloem sieve tubes by an osmotically generated pressure gradient between source and sink tissues. In many plants, source pressure results from thermodynamically active loading in which energy is used to transfer sucrose (Suc) from mesophyll cells to the phloem of leaf minor veins against a concentration gradient. However, in some species, almost all trees, correlative evidence suggests that sugar migrates passively through plasmodesmata from mesophyll cells into the sieve elements. The possibility of alternate loading mechanisms has important ramifications for the regulation of phloem transport and source-sink interactions. Here, we provide experimental evidence that, in gray poplar ( Populus tremula × Populus alba ), Suc enters the phloem through plasmodesmata. Transgenic plants were generated with yeast invertase in the cell walls to prevent Suc loading by this route. The constructs were driven either by the constitutive 35S promoter or the minor vein-specific galactinol synthase promoter. Transgenic plants grew at the same rate as the wild type without symptoms of loading inhibition, such as accumulation of carbohydrates or leaf chlorosis. Rates of photosynthesis were normal. In contrast, alfalfa ( Medicago sativa ) plants, which have limited numbers of plasmodesmata between mesophyll and phloem, displayed typical symptoms of loading inhibition when transformed with the same DNA constructs. The results are consistent with passive loading of Suc through plasmodesmata in poplar. We also noted defense-related symptoms in leaves of transgenic poplar when the plants were abruptly exposed to excessively high temperatures, adding to evidence that hexose is involved in triggering the hypersensitive response.